Poppera trzeci świat okiem życzliwego krytyka - Stępnik, Andrzej (Filozofia Nauki, 2006)
In the first part of the paper, the author presents Popper's theory of the objective knowledge and the three worlds in ten theses with a commentary, showing difficulties and vagueness of Popper's theory and trying to clarify it. The second part comprises discussion with a few Popper's theses. The author especially argues against the thesis about autonomy of the third world, and about epistemology limited to examination of only the objects from the third world. In relation to this, the author shows some defects of Popper's argumentation from Objective Knowledge. The conclusion of the article is a different interpretation and an anew formulation of Popper's theory.